Clinical leadership competency: newly qualified nurses' understanding and needs - Mathumo-Githendu, Gugulethu Waige (My University, 2018)
Clinical leadership is essential for safe, effective and sustainable nursing services. The aim of this study was to establish the newly qualified nurses‟ understanding of clinical leadership and then explore their competency needs. This qualitative study used a convenience sample of 35 newly qualified nurses who were interviewed using a semi-structured interview guide. Template and content data analysis were used as well as the clinical leadership competency framework to identify a priori codes. Only one of the themes on the template was on average mentioned by 50% of the participants while the rest of them had scores below 50%. The competency needs that emerged included continuing personal development support in working with teams, applying knowledge and evidence as well as use of power and authority in setting direction. This study showed that newly qualified nurses have a limited understanding of clinical leadership and they have competency needs that can be addressed in nursing education curricula.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Nursing Science (Nursing Education). Johannesburg, 2018.
Keywords: Clinical Leadership; Nurses